Digital Literacy: Utilization of Social Media as a Media for Course Assignments for Indonesian Language and Literature Education Students - Suryani, Suryani; Fitriyah, Lailatul; Mardiansya, Dedi; Pratami, Fisnia (Procedia of Social Sciences and Humanities, 2024)
This research aims to describe various forms of social media content that can be utilized as assignments in the teaching of Indonesian language and literature. The method used is qualitative descriptive with data analysis techniques employing literature review. The main focus of this study is to provide a concrete overview of assignments that can generate a product from students. The results categorize assignment types based on stages in UKBI (Indonesian Language Ability Test) and identify 10 types of content that can be adapted into Indonesian language and literature materials. The conclusion drawn from this research is that social media can serve as an excellent assignment medium with various contexts that can be creatively, innovatively, interactively, and productively developed.